Infertilitas sebagai Alasan Khulu Perspektif Maqāṣid al-Syarī’ah: Infertility as a Reason for Khulu Perspective of Maqāṣid al-Syarī'ah - Bakry, Kasman; Awal Rifai (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2025)
This study aims to explore how infertility can be used as a legitimate reason for khulu' in terms of maqāṣid al-Syarī'ah, and how sharia principles can provide wise and fair guidance in this situation. This study uses a qualitative descriptive research type (non-statistical) that focuses on literature research with normative and conceptual approaches. The results of the study are as follows; First, Islamic scholars have different opinions regarding infertility which is used as a reason for khulu' (divorce lawsuit by the wife). Some scholars allow it and some do not. The Ḥambali school of thought allows khulu' due to infertility in each marriage partner. Meanwhile, the scholars of the Sāfi'iyyah and Ḥanafiyyah schools of thought are of the opinion that it is not permissible to ask for khulu' from an infertile husband because what allows khulu' is the husband's inability to provide his wife's rights in the form of intimate relations. However, contemporary scholars such as Abdullah ibn Bāz and Ibn al-Qayyim allow it. Second, in the view of maqāṣid al-Syarī’ah, khulu’ caused by infertility aims to maintain the five main objectives of maqāṣid al-Syarī’ah especially Ḥifẓ al-Nasl (preserving offspring). The proposed khulu’ is one form of preserving offspring in infertile couples. Based on the fatwa of scholars, infertility sufferers are allowed to separate from their partners in order to remarry someone else to have offspring. However, before separating, it is better to try medical or non-medical therapy first. The implications of this research are expected to be a reference, literature or consideration for the academic world, and can be a positive reference material and information for the community.